KERAGAAN AGROINDUSTRI DAN POSISI PRODUK BERDASARKAN SIKLUS HIDUP PRODUK PADA SOSIS GULUNG VARIAN NOODLE DI CV CUCURUTUKU CERIA - Meliani Indah Sari; Dyah Aring Hepiana Lestari; Wuryaningsih Dwi Sayekti (Lampung University, 2021)
This study aims to analyze the process production of sausage noodle roll, the income and production costs, the marketing action and determine the position based on the life cycle of sausage noodle roll as well learn the role of supporting service for sausage noodle roll in CV Cucurutuku Ceria. This research method is a case study. The determination of consumer samples is taken by Convenience Sampling. Analysis of the data used in this research is descriptive qualitative and quantitative analysis. The data of this study was collected in May 2019 until June 2019. The results showed that the value R/C>1, that means sausage noodle roll business was profitable. Calculation of the cost of production on sausage rolls noodles amounted to Rp1,046.53. The BEP unit calculation has been achieved for a long time, in the amount of 42,791 units from the BEP calculation of 604 units. The noodle rolls sausage has also obtained a profit from the selling price of Rp ,000.00 per pcs from the calculation of the BEP price of Rp1,238.58 per pcs. The marketing mix that has been utilized by CV Cucurutuku Ceria is collaboration with e-commerce companies namely gofood and grabfood to facilitate consumers in the ordering process and CV Cucurutuku Ceria has utilized social media as promotional activities for sausage noodle roll product. In the product life cycle, sausage noodle roll are in a stage of decline. CV Cucurutuku Ceria has not fully utilized the government policies regarding the protection and empowerment of Micro, Small and Medium Enterprises.Keywords: cost, noodle, position, and sausage